2018
DOI: 10.12659/msm.910735
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Combination Stereotactic Body Radiotherapy Plus High-Intensity Focused Ultrasound Ablation Versus Stereotactic Body Radiotherapy Alone for Massive Hepatocellular Carcinoma

Abstract: BackgroundThermal high-intensity focused ultrasound ablation is a non-invasive treatment of massive hepatocellular carcinomas. In stereotactic body radiotherapy, ablative radiotherapy is administered to tumors in targeted, limited doses to minimize damage to nearby tissues. We evaluated the outcomes and survival of patients receiving stereotactic body radiotherapy (singular therapy) versus those receiving combination thermal high-intensity focused ultrasound ablation plus stereotactic body radiotherapy (combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Similarly, Liu et al [34] reported that a combined treatment of FUS-ablation and RT is more effective for the induction of injury in the swine pancreas compared to a single treatment. In addition, clinical evidence showed that the combination of HIFU ablation and stereotactic body radiation therapy increases the treatment efficiency in massive hepatocellular carcinomas and that the survival rates of patients were significantly enhanced compared to single treatment [35]. The future perspective of using FUS heating as an adjuvant to radiotherapy includes the idea of being able to reduce the radiation dose compared to radiation alone, e.g., only half or one-third to achieve the same effects with fewer side effects, or to have the option to re-irradiate.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Liu et al [34] reported that a combined treatment of FUS-ablation and RT is more effective for the induction of injury in the swine pancreas compared to a single treatment. In addition, clinical evidence showed that the combination of HIFU ablation and stereotactic body radiation therapy increases the treatment efficiency in massive hepatocellular carcinomas and that the survival rates of patients were significantly enhanced compared to single treatment [35]. The future perspective of using FUS heating as an adjuvant to radiotherapy includes the idea of being able to reduce the radiation dose compared to radiation alone, e.g., only half or one-third to achieve the same effects with fewer side effects, or to have the option to re-irradiate.…”
Section: Discussionmentioning
confidence: 99%
“…They found significantly better OS results in those receiving the combined treatment than in those receiving TACE alone. A study showed that the one-year survival rate in the ablation plus stereotactic body radiotherapy (SBRT) cohort was 87%, which was overmatched in the SBRT-only group [ 21 ]. Another study demonstrated that TACE following percutaneous microwave coagulation therapy in HHCC patients was an ideal treatment strategy.…”
Section: Discussionmentioning
confidence: 99%
“…As a summary of previous studies ( Table 5), HIFU has commonly been used for HCC as monotherapy (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) or in combination with other therapies, such as TACE (34)(35)(36)(37)(38)(39)(40)(41)(42), cryocare knife (65), and SBRT (63,66). However, very few studies have reported the efficacy of HIFU monotherapy in patients with MLC (20, 24, 43-47) without any HIFU-based combination regimens reported.…”
Section: Discussionmentioning
confidence: 99%